Medicine and health sciences at IIUM-the Kuantan campus - Azhar, Md. Tahir (IIUM Press, 2009)
Introduction: uslims have always been at the forefront of medical practice, education and research. The spread of Islam coincided with the preservation of the 'lost' art of Greco-Roman medical practice and pharmacopoeia which primarily came from a set of pagan beliefs and practices. The Muslims developed them into an actual science incorporating the art of patient care, medical experimentation, medical ethics, clinical etiquette and acumen. In short, Islam and the Muslims preserved, transmitted and improved these pagan practices and turned them into the science that it is today.